STABILITY OF METAL SINGLE BELT MESH DOMES WITH INITIAL IMPERFECTIONS (Collection of scientific works «Modern structures of metal and wood», 2019)
Recently, in the practice of constructing large-span spatial coatings, shallow mesh domes  have  been  used  more  often  than  others.  Such  designs  make  it  possible  to  form  a  smaller building volume, but their work under the influence of loads is much more complicated. And now the problems of calculating the stability of such domes are not sufficiently solved. The main reason is the difference between the experimental results and the performed calculations. The actual shape and  position  of  the  nodes  of  the  mesh  dome,  as  well  as  its  actual  stress-strain  state  during exploitation, differ from the state performed by the project. Accumulated deviations of the surface geometry  of  the  dome  during  installation,  manufacturing  defects  significantly  change  the  ideal design scheme, which was used in the calculations, and increase the probability of loss of stability. The  stability  of  shallow  metal  single-belt  mesh  domes  with  initial  shape  imperfections obtained in the process of erection of the structures is considered.  The  mesh  dome  was  replaced  with  a  continuous  one  and  its  nonaxisymmetric  deformation with loss of stability from bifurcation loads was analyzed. The  classification  of  the  initial  imperfections  obtained  by  the  structure  during  construction and mounting and the deviations of the loads applied to the structure is given. It is shown that the greatest influence on the loss of stability of a shallow spherical dome has imperfections in the shape of the middle surface. The  approaches  that  lead  to  the  convergence  of  discrepancies  between  the  results  of experimental critical loads of stability loss and theoretical are determined. In calculating stability, it is most important to take account of the initial imperfections of the form and the nonaxisymmetric deformation of the spherical dome, taking into account imperfections. For  engineering  calculations,  the  stability  loss  of  shallow  mesh  domes  is  obtained  by  a dependence that allows you to adjust the critical load to take account the amplitude of the measured initial imperfections of the constructed structure.  For  the  purpose  of  further  research,  it  is  important  to  investigate  the  effect  of  artificially created initial deviations of the  mesh dome nodes  from the  ideal spherical shape  in the direction opposite  to  the  loss  of  stability,  due  to  which  a  significant  increase  in  the  critical  load  can  be achieved.